Lecturers’ and Students’ Perceptions and Acceptance of Artificial Intelligence in Arabic Learning - Rahmida; Nuruddaroini, M. Ahim Sulthan; Syihabuddin, M. (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The rapid advancement of digital technology has transformed educational practices, including Arabic language learning in higher education. However, limited studies have examined user acceptance of Artificial Intelligence (AI) within Islamic higher education contexts. This study aims to investigate lecturers’ and students’ perceptions and the factors influencing AI acceptance in Arabic language learning at STIQ Amuntai. This research employed a descriptive qualitative approach involving lecturers and students as participants. The findings indicate a high level of AI acceptance, primarily influenced by perceived usefulness and ease of use. Lecturers emphasized strategic and pedagogical benefits, while students highlighted efficiency and learning support. Nevertheless, concerns regarding academic integrity and the accuracy of linguistic outputs remain significant challenges. In conclusion, AI plays a crucial role in contemporary language education. Strengthening digital literacy is essential to ensure its critical, ethical, and responsible use.